วิกฤตจิตรกรรมฝาผนังอีสาน - เย็นเฉื่อย สำรวย (Journal of Fine and Applied Arts Khon Kaen University, 2015)
The crisis of Isan Murals is the survey Isan Mural from temples of Tai- Laos ethnic groups in the central of Isan. There are total 13 temples which are based in Khon Kaen, Mahasarakam, Roi-ed and Bureerum province. The researcher applied methods by Visual Diagnosos and In-depth interview key persons. The results of the study were revealed the crisis of Isan Murals cause from the following several reasons; 1. The crisis of Isan Murals cause from degeneration of materials to build Sim and materials to create Murals art works. This cause makes colorûs layers of murals are thinned, rubbed, and come off. 2. The crisis of Isan Murals cause from demolition Sim. The Murals has to be rid off together with the demolition which is the worst crisis of murals. 3. The crisis of Isan Murals cause from natural environment which are sunlight, rain, flood, and salty soil which make colorûs layers of murals are thinned, rubbed, and come off. 4. The crisis of Isan Murals cause from animals which inhabit in Sim. Animaûs trails construction and animalûs stool dropping make murals become dirty and covered the colorûs layers of murals. 5. The crisis of Isan Murals cause from people. People can destroy the murals both direct and indirect ways or intend and do not intend by scraping, scratching, erasing, drawing over the original murals, and restoration without knowledge. This is because receiving of new values and lacking of understanding in valuable of local arts which are creation works of ancestors.